DEVELOPMENT OF SCIENCE MODULE BASED ON ETHNOSCIENCE OF BRICK PROCESSING ON THE MATERIAL OF SUBSTANCE FORM CHANGE - Rahmawati, Amalia Indah; Noor, Faiq Makhdum (Universitas Muhammadiyah Mataram, 2025)
The background of this research is based on the importance of integrating local wisdom in science learning to make it more contextual and meaningful. The formulation of the research problem includes how to develop a module, how the module's feasibility is based on validation by media experts and material experts, and how students and teachers respond to the module. This research aims to develop an ethnoscience-based science learning module by highlighting the local potential of the brick center in Prambatan, Kaliwungu, Kudus as a learning context on the material of substance form change, to determine the feasibility of the module based on validation by media experts and material experts, and to determine students and teachers responses to the module. The method used is research and development (Research and Development) with a 4D model (define, design, develop, disseminate), but this research is only carried out until the development stage due to time constraints. The module development process includes the needs analysis stage, module design, validation by media experts and material experts, revision of validator input, and limited trials for grade VII D students at MTs NU Nurul Huda Kedungdowo Kaliwungu Kudus. The research population is all grade VII students at MTs NU Nurul Huda which totals 270 students. The sampling technique used random sampling by selecting 22 students as limited trial subjects. Data analysis uses qualitative descriptive and uses the Content Validity Index (CVI) technique which is then calculated using the Gregory validity technique which shows a high level of validity with scores of 0.70 (media) and 0.60 (material) respectively. The limited trial involved 22 students and one science teacher with student response results showing a very high level of feasibility (average 88.00%) and the response of science teachers showing a very high level of feasibility (average 97.5%). This module succeeds in integrating the values of local wisdom into science learning so that it can strengthen the relationship between science and daily life.